Transfer Pricing, Thin Capitalization terhadap Effective Tax Rate dengan Sales Growth sebagai Variabel Moderasi pada Perusahaan Properti dan Real Estate - Ramadhani Nufitria; Vidiyanna Rizal Putri; Rachmat Pramukty (Jurnal Kendali Akuntansi, 2026)
This study aims to examine the effect of Transfer Pricing and Thin Capitalization on the Effective Tax Rate (ETR) and to investigate the moderating role of sales growth. This research employed a quantitative approach using secondary data from the annual financial statements of property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A total of 355 observations were selected using purposive sampling. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 13. The results indicate that Transfer Pricing has no significant effect on the Effective Tax Rate, while Thin Capitalization has a positive and significant effect on the Effective Tax Rate. Furthermore, sales growth does not significantly moderate the relationship between Transfer Pricing and Thin Capitalization on the Effective Tax Rate. These findings provide insights for companies in formulating tax policies and serve as a reference for future research on the determinants of the Effective Tax Rate.